Analisis Kelayakan Finansial Usahatani Jeruk Pamelo di Kelurahan Attangsalo Kecamatan Ma’rang Kabupaten Pangkep - Marhawati Marhawati (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the financial feasibility of the Pamelo orange farming in Attangsalo Village, Ma'rang District, Pangkep Regency.  This research is a quantitative research with a descriptive approach. The population of Pamelo orange farmers is 224 people. From this population, a sample of 10% was taken using a simple random sampling method, as many as 22 people of Pomelo orange farmers. The analysis used in this study is the Financial Feasibility Analysis which consists of Net Present Value (NPV), Net Benefit-Cost Ratio (Net BCR) and Internal Rate of Return (IRR).  The results showed that the Pomelo orange farming was feasible to be cultivated, evidenced by the Net Present Value (NPV) obtained was positive, the IRR was greater than the interest rate prevailing at the time the Pomelo orange farming was cultivated and the Net B / C Ratio had more value big than one.